The development of second language projects - Lozada Trimbath, Minnie (1998)
Reflecting on the way we have been working in the language line at school, we teachers have a series of questions about different proposals for change in our teaching practice. In this opportunity, we are going to refer to one aspect of the aforementioned line, the second language (L2) component in intercultural bilingual education. And within this line, the possibility of using the L2 in projects that students will develop in their educational practice.